Responsibilities, rights and restorative justice - Ashworth, Andrew (The British journal of criminology, 2002)
Restorative justice is much advocated as a new and fruitful response to offending. This article argues for further debate about the proper division of functions between state, victims, offenders and communities', and for greater emphasis upon procedural safeguards and substantive limits in the pursuit of the apparently beneficent goals of restorative justice